Fisherman Resilience during The Covd-19 Pandemic Ujung District Parepare Town - Kasdir, Paramitha Sari; Fachry, Mardiana E.; Cangara, Arie Syahruni; Baso, Aris; Gosari, Benny Audy Jaya (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
This study aims to determine the economic condition of fishermen's households, Ujung Kota Parepare District during the Covid-19 pandemic and to determine the resilience of fishermen in meeting their needs during the Covid-19 pandemic. This research was conducted from July 2021 to August 2021. The sampling method is purposive sampling with a total sample of 29 people. The data sources used are primary data and secondary data. Data is analyzed using revenue analysis, and qualitative data analysis. The economic condition of fishing households in Ujung Kota Parepare District during the Covid-19 pandemic has decreased income and seeks additional income by doing side jobs. The resilience of fishermen in Ujung Kota Parepare District in fulfilling the needs of life is to utilize livelihood assets (natural, human, physical, financial and social), which they have in the fishermen households of Ujung District. This capital is used so that fishermen in Ujung District can be resilient during the Covid-19 pandemic without having to increase their burden and vulnerability.